30. PATIENT SAFETY CULTURE IN VAN HANH GENERAL HOSPITAL, HO CHI MINH CITY IN 2023 (Vietnam Journal of Community Medicine, 2024)
Introduction: Patient Safety Culture (PSC) is one of the priorities of interventions in the medical environment towards the goal of “doing no harm to the patient”.Objectives: This study was conducted to assess the current situation of PSC at Van Hanh general hospital, Ho Chi Minh City in 2023.Methods: We applied a cross-sectional design to perform self-administered interviews with 365 health providers in Van Hanh general hospital, Ho Chi Minh City during May-June, 2023.Findings: The positive rate of PSC was 70.9%. The four dimensions with lowest positive rate were Human Resources of the Faculty/Department (51%) and Non-aggressive behavior by the Faculty/ Department (49.1%), followed by Communication Opennness (62.1%), and Handover and transfer (68.6%).Conclusions: 4/12 dimensions of PSC got low positive rate. Our study recommends to improve the evaluation and working environment with openness in reporting medical errors.
Keywords: Patient safety culture, medical error, Van Hanh general Hospital.